The effect of heavy-resistance core strength training on upper-body strength and power performance in national-level junior athletes-a pilot study - Saeterbakken, A. H.; Sandvikmoen, T. E.; Iversen, E.; Bjørnsen, T.; Stien, N.; Andersen, V.; Scott, S.; Prieske, O. (Frontiers in Physiology, 2025)
Introduction: The concept of core strength refers to the ability of the core muscles to transfer, absorb and re-direct energy, and generate force/torque while providing proximal stability for distal mobility of the limbs. The aim of the present study was to examine the effects of an 8-week heavy-resistance core strength training (HR-CST) program on upper-body strength and power performance in young athletes. The secondary aim was to examine the role of sport-specific training background (kayak sprinters vs. swimmers) and sex (males vs. females).